2015
DOI: 10.1080/17470919.2015.1059361
|View full text |Cite
|
Sign up to set email alerts
|

Early and late event-related potentials are modulated by infant and adult faces of high and low attractiveness

Abstract: 1The processing of infant faces may be somewhat distinct from that of adult 2 faces. Indeed, recent neuroimaging studies have provided evidence of an 3 early, "baby-specific" neural response whereby infant faces are perceived 4 more rapidly than adult faces. Using event-related potentials, the present 5 study aimed to determine whether the preferential response to infant faces is 6 present at both early and late stages of face processing, and to investigate 7 the effects of aesthetic appearance on the processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 72 publications
10
36
1
Order By: Relevance
“…The modulation of both early and late ERP components may indicate that infant faces garner heightened initial and sustained attentional resources that serve to facilitate an adaptive caregiving response (see Maupin et al , 2015). However, whereas Hahn et al (2016) found that early and late ERP components were modulated by infant faces regardless of participant gender, we found that this preference was gender-specific for select ERPs. Specifically, P1 and LPP amplitudes were larger in response to infant than adult faces for females only, suggesting a unique advantage for women in the early processing of infant faces and sustained attention thereof.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The modulation of both early and late ERP components may indicate that infant faces garner heightened initial and sustained attentional resources that serve to facilitate an adaptive caregiving response (see Maupin et al , 2015). However, whereas Hahn et al (2016) found that early and late ERP components were modulated by infant faces regardless of participant gender, we found that this preference was gender-specific for select ERPs. Specifically, P1 and LPP amplitudes were larger in response to infant than adult faces for females only, suggesting a unique advantage for women in the early processing of infant faces and sustained attention thereof.…”
Section: Discussioncontrasting
confidence: 99%
“…As expected and in line with previous findings (e.g. Proverbio et al , 2011; Hahn et al , 2016), the P1, N170, P2 and LPP each evidenced a bias to infant over adult faces. Unlike in previous studies, these results were demonstrated while considering the effect of emotional facial expression (happy vs sad), which suggests that—even in the presence of other salient facial cues—the adult brain rapidly processes and prioritizes infant face characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Cute-emotion is principally a response to neotenic or baby-animal characteristics, such as big round eyes, small size, and softness. These characteristics are involved in human mate selection (Jones and Hill, 1993; Jones et al, 1995; Perrett et al, 1998; Thayer and Dobson, 2013) and human parental care (Sherman et al, 2009; Nittono et al, 2012; Sprengelmeyer et al, 2013; Aragón et al, 2015; Golle et al, 2015; Hahn et al, 2016; though see also Sherman and Haidt, 2011). …”
mentioning
confidence: 99%